Coseismic and postseismic motion of a landslide: Observations,modeling, and analogy with tectonic faults - Lacroix, Pascal (2014)
We document the first time series of a landslide reactivation by an earthquake using continuous GPS measurements over the Maca landslide (Peru). Our survey shows a coseismic response of the landslide of about 2 cm, followed by a relaxation period of 5 weeks during which postseismic slip is 3 times greater than the coseismic displacement itself. Our results confirm the coseismic activation of landslides and provide the first observation of a postseismic displacement. These observations are consistent with a mechanical model where slip on the landslide basal interface is governed by rate and state friction, analogous to the mechanics of creeping tectonic faults, opening new perspectives to study the mechanics of landslides and active faults.